Determinants of Iain Palopo Student Interest in BSI Mobile Services in The Covid-19 Pandemi - Cahayani Cahayani (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
This study aims to find out whether the convenience, benefits, and safety affect IAIN Palopo students' interest in using BSI Mobile services during the Covid-19 pandemic. The data collection technique in this study used a questionnaire distributed online with a population of all Islamic banking students class of 2017 at the Faculty of Economics and Business at IAIN Palopo. The sampling technique used accidental sampling using the slovin formula, namely 67 people. The research method used was multiple regression analysis with the help of SPSS version 22 software. The results of the study were (1) convenience (X1) with a tcount of 2.916 > ttable of 1.999 and a significant level of 0.005 <0.05. (2) benefits (X2) with a tcount of 2,412 > ttable of 1.999 and a significant level of 0.019 <0.05. (3) security (X3) tcount 2.042 > t table 1.999 and a significance level of 0.045 < 0.05. so that it can be concluded that these three variables partially had a positive and significant effect on students' interest in using BSI mobile services during the Covid-19 pandemic. (4) convenience, benefits, and safety simultaneously have a positive and significant effect on students' interest in using BSI Mobile services during the Covid-19 pandemic with an F count of 33,164 and a significance value of 0.000 (<0.05). The coefficient of determination (R2) is 0.625.